(untitled) (Nonlinear Studies, 2013)
We consider the problem of insensitizing control when the control is subject to a finish number of linear constraint. We prove the existence of such control by solving a problem of null controllability with constraint on the control. The key of our results is an observability inequality of Carleman type adapted to the constraints.